Effects of ischemic compression of trigger points in painful episodes of patients with chronic shoulder pain. Systematic Review. - Paz, Isabel de Almeida; Kerppers, Ivo Ilvan; Fréz, Andersom Ricardo (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Disorders of the shoulder are the major musculoskeletals morbidities, whose pathophysiological mechanisms of pain in the shoulder are poorly understood, myofascial trigger points are presented as alternative diagnosis of these disorders. Objective: To investigate the effectiveness of the release of trigger points on the pain symptoms in patients with chronic shoulder pain. Method: We conducted a descriptive study using a systematic literature review, in consultation with the databases PubMed, EMBASE, CINAHL, PEDro, SportDiscus, and LILACS . Two reviewers assessed the methodological quality of the selected studies, with the help of Quality Scale Jadad and PEDro scale. Results: The initial search resulted in 312 articles . After analyzing the titles and reading the abstracts, 70 studies that appeared repeatedly in more than one database and 214 who did not meet the predefined inclusion criteria, 28 texts were analyzed in their entirety were excluded, considering the inclusion and exclusion criteria defined only 2 articles were selected and subjected to analysis for methodological quality. Conclusion: The results demonstrate the importance of inspection and inactivation of myofascial trigger points in the muscles of the shoulder in patients with chronic pain, as they contribute to decreased overall picture of pain.